A iniciação infantil à flauta transversal a partir do pífaro: repertório, aspectos técnicos e recursos didáticos - Alberto Sampaio Neto (2005)
This dissertation studies childrens introduction to Flute learning and proposes the use of Pífaro flute (Yamaha-fife) in the first stages. The main technical aspects that are worked at the beginning stage were approached in detail. These are: the way of holding the instrument, sound emission (embouchure and blowing), tonguing and fingering (mechanism). Some didactic tools (materials and activities) werespecifically selected and elaborated in order to work each one of these aspects. In this process, directives of the Musical Education area such as diversity and creativity were taken into account. Also, various methods for Flute teaching as well as one specific for the teaching of the Pífaro were analyzed in order to help set the groundings for this study. Thirty-five pieces of music, mainly Brazilian, were selected and analyzed so as toform a broad and diversified repertoire which could be appropriate for the use of Pífaro at the beginning of the learning process. An analysis, by topics, was made for each one of them, evaluating its didactic potential. In order to establish referential parameters that could provide a notion of progressiveness to the repertoire, twentyeight technical-musical aspects were defined, together with their respective complexity factors. This research also presents two important didactic resources, which were elaborated and developed to be used at the first stages of learning an instrument: the recordings containing the accompaniments (all pieces of music of the repertoire were recorded on a CD) and the graphical scores (using non-conventional notation).